Fra Angelico - Verdon, Timothy (Arts and the sacred, 2020)
A lavishly illustrated exploration of the art and theology of Fra Angelico. Fra Angelico offers a unique encounter with the celebrated painter, seen through the eyes of Monsignor Timothy Verdon. As an art historian and (like Angelico) a Catholic priest, Monsignor Verdon approaches the work of the only artist ever beatified through the theological lens it deserves, bringing together Fra Angelico's art and his faith.Praised by his contemporaries, by later art historians, and by generations of viewers, Fra Angelico's art is known for its exceptional combination of piety and painterly skill. In this book, Monsignor Verdon explores the spiritual and mystical foundations of the friar-painter's work, and traces his artistic evolution from his early work, to the frescoes for the covent of San Marco in Florence, his Annunciations, and the chapel for Pope Niccol©ø V.Lavishly illustrated with over 200 high-quality images, Beato Angelico illuminates Fra Angelico's art and his faith.
Keywords: Angelico, : fra, : approximately 1400-1455; Art, Renaissance : Italy